3D time‐varying simulations of Ca2+ dynamics in arterial coupled cells: A massively parallel implementation. (1st July 2016) - Zakkaroff, Constantine; Moore, Stephen; Dowding, Stewart; David, Tim
Summary: Preferential locations of atherosclerotic plaque are strongly associated with the areas of low wall shear stress and disturbed haemodynamic characteristics such as flow detachment, flow recirculation and oscillatory flow. The areas of low wall shear stress are also associated with the reduced production of adenosine triphosphate in the endothelial layer, as well as the resulting reduced production of inositol trisphosphate (IP 3 ). The subsequent variation in Ca 2+ signalling and nitric oxide synthesis could lead to the impairment of the atheroprotective function played by nitric oxide. In previous studies, it has been suggested that the reduced IP 3 and Ca 2+ signalling can explain the correlation of atherosclerosis with induced low WSS and disturbed flow characteristics. The massively parallel implementation described in this article provides insight into the dynamics of coupled smooth muscle cells and endothelial cells mapped onto the surface of an idealised arterial bifurcation. We show that variations in coupling parameters, which model normal and pathological conditions, provide vastly different smooth muscle cell Ca 2+ dynamics and wave propagation profiles. The extensibility of the coupled cells model and scalability of the implementation provide a solid framework for in silico investigations of the interaction between complex cellular chemistry and the macro‐scale processes determined by fluid dynamics. © 2016 The Authors. International Journal for Numerical Methods in Biomedical Engineering published by John Wiley & Sons Ltd. Abstract : This research presents a massively parallel framework for performing simulations of coupled endothelial and smooth muscle dynamics in a bifurcating artery. The simulations reported in this work include up to 2.3 million cells modelled by more than 20 million ordinary differential equations. The results of our simulations show a radically varying range of Ca 2+ wave propagation profiles determined by the cell coupling configurations. The simulations demonstrate that heterotypic 2+ diffusion through gap junctions is the dominant mass transport mechanism.